2017
DOI: 10.5336/biostatic.2016-54437
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel Logistic Regression Analysis of the Determinants of Stillbirth in Ethiopia Using EDHS 2011 Data

Abstract: Objective: Stillbirth is often defined as fetal death after 24 weeks of gestation, but a fetus greater than any combination of 16, 20, 22, 24, or 28 weeks gestational age and 350g, 400g, 500g, or 1000g birth weight may be considered stillborn depending on local law. Once the fetus has died, the mother may or may not have contractions and undergo childbirth or in some cases, a Caesarean section. Most stillbirths occur in full-term pregnancies. If all causes of stillbirth are taken together, the new estimates w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…Visiting antenatal care for at least once is found to decrease the probability of experiencing adverse pregnancy outcome. Similarly, the finding is correspondence with previous study [15]. Study done in Wollo showed that, Mothers who didn't attend ANC were more than 3 times to have adverse pregnancy outcome, than mothers who attended ANC follow up, OR=3.4.…”
Section: Discussionsupporting
confidence: 90%
“…Visiting antenatal care for at least once is found to decrease the probability of experiencing adverse pregnancy outcome. Similarly, the finding is correspondence with previous study [15]. Study done in Wollo showed that, Mothers who didn't attend ANC were more than 3 times to have adverse pregnancy outcome, than mothers who attended ANC follow up, OR=3.4.…”
Section: Discussionsupporting
confidence: 90%
“…So, all of these articles are subject to an atomistic or ecological fallacy [17,21,22,[29][30][31][32][33][34][35][36][37][38][39]. The factors associated with the unmet need to FP are area-specific which requires a different approach of analysis at a different level [8,24,[40][41][42][43][44][45][46]. So, this study took into account those different levels of analysis and aimed to assess individual and community-level factors associated with unmet need for contraception among reproductive-age women in Ethiopia (EDHS 2016 dataset, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Those children born from anemic women were found more likely to be stunted and underweighted, low birth weight and intrauterine growth restriction [14][15][16][17][18]. It also found to cause perinatal death [12,[19][20][21][22], delay in cognitive and motor development [23][24][25] and dementia [26]. Anemia in the mother during pregnancy also resulted in anemia in the newborn baby [27,28].…”
Section: Introductionmentioning
confidence: 99%